The natural history of lakes - Burgis, Mary J. | Morris, Pat (Cambridge University Press / New York, 1987)
Contents: Lakes in the landscape; Lake water; Lake communities; Lakes and the season; Polar and mountain lakes; The despest lakes; Shallow Lakes